2013
DOI: 10.4028/www.scientific.net/amm.465-466.242
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Dual Powered Mini Pelletizer

Abstract: Wood pellets are compressed wood particles that are used as fuel. Pellets are gaining popularity and are commonly used in some areas of India owing to the cost effectiveness. One of the major reasons is the increase in the cost of primary fuels and concerns about global climate change. For research and development work and for the production of small quantities of pellets for specific applications, it is important to have a low-cost apparatus or machine for making pellets. The paper discusses the local design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Where it is also observed that leptochloa fusca is harder and cannot be cut or touched by hand. Dual powered (electrical and manual power) mini pelletizing machine was designed and fabricated [1].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Where it is also observed that leptochloa fusca is harder and cannot be cut or touched by hand. Dual powered (electrical and manual power) mini pelletizing machine was designed and fabricated [1].…”
Section: Background and Literature Reviewmentioning
confidence: 99%